Abstracts of the Nobel Week 2021 organized at Villa Nobel in Sanremo, Italy; Villa Nobel, Sanremo (Italy); December 11, 2021 - - (Hygeia Press di Corridori Marinella, 2021)
Abstracts of the Nobel Week 2021 organized at Villa Nobel in Sanremo, Italy   NEW FRONTIERS IN PEDIATRICS [NUOVE FRONTIERE IN PEDIATRIA]   Villa Nobel • Sanremo (Italy) • December 11th, 2021   The meeting has been organized by the Alfred Nobel's Friends International Association and Centro Studi Alfred Nobel's Friends Sanremo in collaboration with Prime Quality srl.   ABS 1. NEW EXTRACTION TECHNOLOGIES FOR THE PRODUCTION OF PHYTOCOMPLEXES AND BIOACTIVE NATURAL COMPOUNDS IN SUBCRITICAL WATER [NUOVE TECNOLOGIE ESTRATTIVE PER LA PRODUZIONE DI FITOCOMPLESSI E COMPOSTI NATURALI BIOATTIVI IN ACQUA SUBCRITICA] • C. Cravotto (Avignon, France) ABS 2. KNOWLEDGE OF THE MICROBIOTA: PERSONAL EXPERIENCE FROM 324 QUESTIONNAIRES ADMINISTERED TO MOTHERS AND MOTHERS-TO-BE [LA CONOSCENZA DEL MICROBIOTA: ESPERIENZA PERSONALE SU 324 QUESTIONARI SOMMINISTRATI A MADRI E FUTURE MADRI] • A.R. Amadei, A.M. Fulghesu, S. Angioni, V. Fanos (Cagliari, Italy) ABS 3. WHAT TO EXPECT FROM THE COVID-19 VACCINE WHEN YOU ARE EXPECTING OR LACTATING WOMEN? SEVEN ANSWERS FOR SEVEN QUESTIONS [COSA ASPETTARSI DAL VACCINO COVID-19 QUANDO SI È IN ATTESA O SI ALLATTA? SETTE RISPOSTE PER SETTE DOMANDE] • F. Bardanzellu, R. Gangi, E. Curridori, V. Fanos, M.A. Marcialis (Cagliari, Italy) ABS 4. HEALTH PROTECTION IN THE WORKPLACE: OCCUPATIONAL MEDICINE FROM ITS ORIGINS TO THE COVID-19 PANDEMIC [LA TUTELA DELLA SALUTE NEI LUOGHI DI LAVORO: LA MEDICINA DEL LAVORO DALLE ORIGINI ALLA PANDEMIA COVID-19] • A. Rahmani, S. Zacconi, B. Kusznir Vitturi, P. Durando (Genoa, Italy) ABS 5. METABOLOMIC PROFILE AND EFFICACY OF PIDOTIMOD IN A PEDIATRIC POPULATION AFFECTED BY PERIODIC FEVER, APHTHOUS STOMATITIS, PHARYNGITIS, ADENITIS (PFAPA): A PILOT, MULTICENTER, OPEN-STUDY [PROFILO METABOLOMICO ED EFFICACIA DI PIDOTIMOD IN UNA POPOLAZIONE PEDIATRICA AFFETTA DA FEBBRE PERIODICA, STOMATITE AFTOSA, FARINGITE, ADENITE (PFAPA): UNO STUDIO PILOTA, MULTICENTRICO, APERTO] • S. Manti, G.F. Parisi, M. Papale, P. Barone, R. Pintus, A. Noto, C. Piras, L. Atzori, S. Leonardi, V. Fanos (Catania and Cagliari, Italy) ABS 6. ALL-ROUND NUTRACEUTICS FOR 21ST CENTURY CHRONIC DISEASE PREVENTION [NUTRACEUTICA A ''TUTTOTONDO'' PER LA PREVENZIONE DELLE MALATTIE CRONICHE DEL XXI SECOLO] • A. Colletti (Turin, Italy) ABS 7. CONGENITAL CYTOMEGALOVIRUS INFECTION IN NEWBORNS: DIFFERENCES IN THE RELATIONSHIP BETWEEN THE VIRUS AND THE HOST'S IMMUNE SYSTEM AS A POSSIBLE EXPLANATION FOR THE DIFFERENCES IN THE CLINICAL PHENOTYPE [L'INFEZIONE CONGENITA DA CITOMEGALOVIRUS NEL NEONATO: IL RAPPORTO TRA VIRUS E SISTEMA IMMUNITARIO DELL'OSPITE COME POSSIBILE SPIEGAZIONE PER LE DIFFERENZE NEL FENOTIPO CLINICO] • A. Spadavecchia, A. Leone, V. Dell'Oste, M. Biolatti, A. Coscia, F. Cresi, C. Peila, C. Rubino, E. Bertino (Turin, Italy) ABS 8. QUALITY OF THE MEDITERRANEAN DIET EDUCATION PROGRAMS, FOR THE HEALTH OF THE NEW GENERATIONS AND SUSTAINABILITY [EDUCAZIONE DI QUALITÀ ALLA DIETA MEDITERRANEA, PER LA SALUTE DELLE NUOVE GENERAZIONI E LA SOSTENIBILITÀ] • D. Meleleo (Canosa di Puglia, Italy) ABS 9. PLASTICS AND PERINATAL HEALTH: BISPHENOL EXPOSURE STUDY IN PREGNANCY AND NEONATAL AGE [MATERIALI PLASTICI E SALUTE PERINATALE: STUDIO DI ESPOSIZIONE AI BISFENOLI IN GRAVIDANZA E IN ETÀ NEONATALE] • S. Sottemano, E. Cartiglia, A. Spadavecchia, V. Belisario, R. Bono, E. Bertino (Turin, Italy) ABS 10. CIRCULAR ECONOMY: REUSE OF VEGETABLE WASTE FOR THE PRODUCTION OF A HEALTHY SNACK [ECONOMIA CIRCOLARE: RIUTILIZZO DEGLI SCARTI ALIMENTARI DI VERDURA PER LA PRODUZIONE DI UNO SNACK SALUTARE] • B. Buronzo, D. Allegri, E. Finocchiaro (San Giusto and Turin, Italy) ABS 11. FROM OMEGA-3s TO RESOLVINS: THE IMPORTANCE OF NUTRITIONAL ADEQUACY IN THE MOTHER AND CHILD DYAD [DAGLI OMEGA-3 ALLE RESOLVINE: L'IMPORTANZA DELL'ADEGUATEZZA NUTRIZIONALE NELLA DIADE MAMMA-BAMBINO] • A. Bosco, R. Pintus, V. Fanos, A. Dessì (Cagliari, Italy) ABS 12. ULTRA-PROCESSED FOODS AND HEALTH OUTCOMES IN MATERNAL-INFANT PAIRS [GLI EFFETTI DEI CIBI ULTRA-PROCESSATI SULLA SALUTE MATERNO-INFANTILE] • R. Pintus, A. Bosco, A. Dessì, V. Fanos (Cagliari, Italy) ABS 13. HEALTH PROTECTION IN THE WORKPLACE: THE 21ST CENTURY SCENARIO [LA TUTELA DELLA SALUTE NEGLI AMBIENTI DI LAVORO: GLI SCENARI DEL XXI SECOLO] • A. Godono (Turin, Italy) ABS 14. CHILDREN WITH LONG COVID-19 SYMPTOMS IN THE PEDIATRIC OUTPATIENT CLINIC [I BAMBINI CON SINTOMI LONG COVID-19 NELL'AMBULATORIO PEDIATRICO] • G. Trapani, G. Verlato, E. Bertino, G. Maiocco, R. Vesentini, A. Spadavecchia, A. Dessì, V. Fanos (Sanremo, Verona, Turin and Cagliari, Italy)